CHA: cross-chain based hierarchical architecture for practicable blockchain regulatory - Pujie JING; Liangmin WANG; Xuewen DONG; Yushu ZHANG; Qian WANG; Sohail Muhammad (Tongxin xuebao)
Researching the problems with blockchain regulation is crucial.In view of this, CHA (cross-chain based hierarchical architecture) was proposed to address the problems in blockchain regulatory, and a “chain of custody-business chain” cross-chain collaboration chain-based regulatory model was designed.The decentralized of information system regulatory was improved by building a decentralized governance chain, which realized regulatory by separating the strategy layer from the regulatory layer and the business layer, and achieved separation of regulatory behavior and regulatory technology, thus ensuring the versatility of the blockchain regulatory structure.Finally, the distributed feasibility of the regulatory framework is demonstrated through a formal analysis method, and then the technical feasibility of the scheme in terms of cross-chain regulatory reliability, general feasibility and scalability applicable to different regulatory services are proved.